ANALISIS SISTEM PENGENDALIAN INTERNAL ATAS SIKLUS PENERIMAAN KAS (Studi Kasus pada RSUD Kabupaten Jombang) - Ningsih, Venia Wahyu; Wijayanti, Anita (Jurnal Ilmiah Mahasiswa FEB, 2014)
This study aims to describe  how internal controls have been applied to the General Hospital of Jombang especially in the cycle of cash receipts. Data collection for this study was done by interview, direct observation and documentation as well as the use of literature related to the  cycle of cash receipts. Results from this study indicate that there are some weaknesses in the internal control Hospital Jombang. Which were related to the absence flowchart cash receipts, and SOP patient enrollment. Therefore, hospitals need to design a system that is more effective and efficient.Key  words:  Systems,  Information,  Accounting,  Internal Control,  Cash Receipt Cycle